2021
DOI: 10.1039/d1ra02118d
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies of maleidride-forming enzymes

Abstract: In vitro synthesis of byssochkamic acid 12 was achieved from hexenoyl CoA 14dvia anhydride 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 48 publications
(61 reference statements)
0
21
0
Order By: Relevance
“…75,90,96,101 Moving beyond the monomer, the core enzyme required for dimerisation, and therefore ultimately controlling the structure of the mature maleidride, is the maleidride dimerising cyclase. 50,75,96,101,105 This coupling reaction appears to be aided by the PEBP-like enzymes, although their exact role is currently obscure. 50,75,96,101,105 The precise detail of how cyclisation is controlled remains cryptic, at present it is not possible to predict whether a biosynthetic gene cluster will deliver dimers showing head-to-head, head-to-tail or head-toside modes of cyclisation, highlighting that there is still much to be discovered in this type of pathway.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…75,90,96,101 Moving beyond the monomer, the core enzyme required for dimerisation, and therefore ultimately controlling the structure of the mature maleidride, is the maleidride dimerising cyclase. 50,75,96,101,105 This coupling reaction appears to be aided by the PEBP-like enzymes, although their exact role is currently obscure. 50,75,96,101,105 The precise detail of how cyclisation is controlled remains cryptic, at present it is not possible to predict whether a biosynthetic gene cluster will deliver dimers showing head-to-head, head-to-tail or head-toside modes of cyclisation, highlighting that there is still much to be discovered in this type of pathway.…”
Section: Discussionmentioning
confidence: 99%
“…12) is essential, as no Interestingly, all conrmed and putative maleidride BGCs contain a hydrolase homologue, suggesting that it is important for the biosynthesis of maleidride compounds. 96 In vitro studies by Cox and co-workers 101 showed that the P. fulvus hydrolase, BfL1, catalysed the hydrolysis of a series of a thiol esters, rather than being ACP-selective, therefore exactly how selectivity is controlled is unknown. 101 Investigations into the ACS and ACDH enzymes through in vitro characterisation have also been reported.…”
Section: Natural Product Reports Reviewmentioning
confidence: 99%
See 3 more Smart Citations